Aplikasi Media Sosial Untuk Para Penggemar Cullinary Berbasis Android - Yoel Tanuwijaya; Andreas Handojo; Kristo Radion Purba (Jurnal Infra, 2015)
Along with the very fast growth of social media, more users use it to share photos/videos about food. Many people use it to store food pictures and recommend the food they like therefore it will make other people want to try it. The high demand of culinary information brings an opportunity for culinary business owner to promote their business through social media. This application can help users and business owners to obtain complete culinary information through photos/videos, address, contacts, menus and trending foods so that it will be easier for them to conduct transactions. The application will also help the user to go to a culinary place they want. This application was built using phonegap on android operating system which is known for easy usage and the most used operating system in the world. The test results show that 73,3% respondents think that this application is really helpful because of it’s high usage and the feature that helps owners to promote and  conduct transactions.